The Development of antioxidant products from Tilapia offal protein hydrolysate with different enzyme concentrations and a review in fulfillment of the halal product assurance criteria - Sholahuddin, Muhammad Athoillah; Prayoga, Adistiar (Universitas Airlangga, 2023)
Tilapia fish meat is a raw material that is widely consumed by the community due to its high nutritional value. However, the amount of meat consumption is not accompanied by the management of tilapia by-products. By-products from the disposal of tilapia processing can cause pollution and disrupt certain ecosystems, so it is necessary to manage the waste by-products of tilapia products. One way to process tilapia offal waste is by utilizing it as a protein hydrolysate product. Protein hydrolysate is a derivative product of protein in the form of bioactive peptides and amino acids that have potential as antioxidants. Products from antioxidants have many benefits such as anti-aging, as food supplements, as drugs to ward off cancer and so on. However, antioxidant products sold commercially are relatively expensive when compared to tilapia offal waste protein hydrolysate products. Therefore, this protein hydrolysate product is a suitable means to be an alternative as a substitute for commercial antioxidants. However, from another perspective, waste that is regarded as inappropriate production residue is really used as a raw material for consumable. Meanwhile, the Indonesia government has legalized law number 33 of 2014 oh Halal Product Assurance, which requires that all products entering, circulating, and traded in Indonesia be halal certified. So, the purpose of this study, (1) investigate the (1) investigate the influence of proteolytic enzymes at different doses on antioxidant activity in tilapia offal waste protein hydrolysate. (2) Review product development to ensure that it meets halal product assurance requirements in Indonesia and becomes a raw material or additional material that can be halal certified